EFFECT OF VITAMIN E (a .. TOCOPHEROL) ON PROTEIN CONTENT OF LABEO ROHITA (HAM.).FRY - SRIVASTAVA, P. P.; JAIN, K. K. (Journal of Indian Fisheries Association, 2015)
Increase in body protein concentration was noted in the fry ofrohu fed vitamin E@ O.Omg, 25mg, 50mg, 75mg, 100mg, 150mg, 200mg,300mg, and 400mg/kg of formulated diet. The protein content of frywas found to be significantly different between the different levels ofvitamin E. It was found to be maximum (18. 7%) in the case of vitaminE @ 75mg/kg diet followed by vitamin-E @lOOmglkg diet. On increasingof vitamin E above 100 mg per kilogram diet there was further declinein the protein content of the fry. The protein increase, from the initialvalue (12.5%), were recorded to be 14.4%, control; 21.6%, 25mg level;31.2%, 50mg level; 49.6%, 75mg level; 45.6%, 100 mg level; 14.4%, 150mglevel; 28%, 200 mg level; 29.6%, 300 mg level and 13.6% for 400 mg levelin different experimental groups